Optimization of Boolean queries in information retrieval systems using genetic algorithms - Genetic programming and fuzzy logic - Owais, S.S.J. (Journal of Digital Information Management, 2006)
This paper proposes to use two information retrieval system models (Boolean information retrieval model and extended Boolean (fuzzy) information retrieval model). These models differ by using Boolean queries or fuzzy weighted queries. It also proposes a way for optimizing user query for the two models by using genetic programming and fuzzy logic. And proposes to use more number of Boolean operators (AND, OR, XOR, OF, and NOT) instead of the standard Boolean operators (AND, OR, and NOT), and use weights for Boolean operators and for terms in fuzzy models.
Keywords: Boolean operator weights; Boolean query; Fuzzy logic; Genetic algorithms; Genetic programming; Information retrieval; Term weights